Further Professional On-the-Job Training of Employees in the Digital Era - Barnová, Silvia; Duda, Małgorzata; Matulčíková, Marta; Gabrhelová, Gabriela; Hrivíková, Tatiana (International Journal of Engineering Pedagogy (iJEP), 2022)
Implementation of new technologies and processes influences the changes of many company processes. Some activities change, new ones appear, and others disappear due to gradual digital transformation. This process does not necessarily lead to complete transformation into a digital environment. Each company is unique therefore, its digital transformation is specific too. The result is a hybrid environment combining the digital and analogue world leading to the necessity to select appropriate employees and prepare their further professional training as well. The employees, on the one hand, must demonstrate certain competencies and experience necessary to make the digital transformation a success story and on the other, they need to be prepared for new digital technologies and modern work processes. The paper characterised the development of employees from the perspective of individual and/or team training. Within this scope, it describes various types of training. The empirical research focuses on the necessity of various training activities and their preference in the period of transforming the economy to Industry 4.0.